Setting health research priorities using the CHNRI method: V. Quantitative properties of human collective knowledge - Igor Rudan 1; Sachiyo Yoshida 2; Kerri Wazny 1; Kit Yee Chan 1,3; Simon Cousens 4 (Edinburgh University Global Health Society, 2016)
The CHNRI method for setting health research priorities has crowdsourcing as the major component. It uses the collective opinion of a group of experts to generate, assess and prioritize between many competing health research ideas. It is difficult to compare the accuracy of human individual and collective opinions in predicting uncertain future outcomes before the outcomes are known. However, this limitation does not apply to existing knowledge, which is an important component underlying opinion. In this paper, we report several experiments to explore the quantitative properties of human collective knowledge and discuss their relevance to the CHNRI method.